Effectiveness of lung ultrasonography for diagnosis of pneumonia in adults: a systematic review and meta-analysis - Xia, Yang; Ying, Yinghua; Wang, Shaobin; Li, Wen; Shen, Huahao (Journal of Thoracic Disease, 2016)
Background: Pneumonia is usually presented as a forgotten killer, and an early diagnosis could largely improve the prognostic outcomes. Lung ultrasound (LUS) has been universally applied in evaluating multiple pulmonary diseases including pneumonia. However, the diagnosis accuracy of LUS for pneumonia in adults is still uncertain. Hence, we performed a systematic review of the current literature to assess the diagnosis accuracy of LUS for pneumonia in adults. Methods: PubMed and EMBASE were searched for clinical trials that assessed the detection accuracy of LUS for pneumonia in adult patients. We extracted descriptive and quantitative information from eligible studies that met strict inclusion criteria and calculated pooled sensitivity, specificity and pooled diagnostic likelihood ratios (LR). Summary receiver operating characteristic (sROC) curve was used to assess the overall performance of LUS-based assays. Results: We reviewed 1,072 articles and selected 38 for detailed review. 14 articles containing 1,911 participants met all inclusion criteria and were included in the final analysis. LUS exhibited a pooled sensitivity of 0.904 (0.884–0.921), specificity of 0.884 (0.861–0.904), positive LR of 6.6 (3.7–11.7), negative LR of 0.08 (0.04–0.19) and the area under curve (AUC) was 0.9611. Interestingly, when CT alone, CT combined with clinical presentations, and microbiology was set as the gold standard of pneumonia respectively, LUS demonstrated a pooled sensitivity of 90.9%, 95.0%, 53.3%, and a pooled specificity of 89.7%, 91.3% and 67.9%. In extension, we compared the diagnostic efficiency of LUS for pneumonia with chest X-ray (CXR) in 1,343 patients. The AUC for LUS and CXR was 0.972 and 0.867 respectively and the Z statistic of the two sROC curves was 2.31. Conclusions: Our study indicated that LUS is a robust diagnostic tool for pneumonia with high accuracy. Utilization of LUS would facilitate the estimation of pneumonia at bedside.